Sweet potato pests: Perspectives on the use of pheromones for control and monitoring - Alves, Josias Jordão Andrade; Silva, Igor Ferreira Pereira; Andrade, Anderson Bruno Anacleto; Da Silva Acácio, Regina; Fonseca Goulart, Henrique; Goulart Santana, Antonio Euzébio (Journal of Plant Protection Research, 2026)
Sweet potato production is mainly concentrated in tropical and subtropical regions, especially in developing countries in Africa, Asia and Latin America. It is a rustic crop fundamental to the population’s food security. More research needs to be conducted on the crop, especially on the chemical ecology of insects that affect the plant. This review shows the main pests that affect sweet potato production and presents insect pheromones and their efficiency in semi-field and field tests with different releasers. Small farmers use cultural, biological, and chemical methods to reduce insect pest damage. With the advancement of new research, behavioral control is a growing practice, e.g., sex pheromones are used to monitor and control pests. This practice is possible because of studies on the chemical ecology of insects. There is a need to use specific and safe low-cost strategies associated with IPM. This review aimed to present a compilation of the leading pheromone options for controlling insects that affect sweet potato production, in order to assist in decision-making in the study of new pheromones from known pests and a combination of pheromones with other control strategies.